Research progress in the mechanism of acupuncture regulating microglia in the treatment of Alzheimer’s disease - Liu, Jia; Zhou, Jiaqi; You, Chong; Xia, Haonan; Gao, Yuling; Liu, Yong; Gong, Xiaoyang (Frontiers in Neuroscience, 2024)
Alzheimer’s disease (AD) is the most common neurodegenerative disease in the central nervous system, characterized by memory and cognitive dysfunction. Acupuncture is an effective means to alleviate the symptoms of AD. Recent studies have shown that microglia play an important role in the occurrence and development of AD. Acupuncture can regulate the activity of microglia, inhibit neuroinflammation, regulate phagocytosis, and clear Aβ Pathological products such as plaque can protect nerve cells and improve cognitive function in AD patients. This article summarizes the relationship between microglia and AD, as well as the research progress in the mechanism of acupuncture regulating microglia in the treatment of AD. The mechanism of acupuncture regulating microglia in the treatment of AD is mainly reviewed from two aspects: inhibiting neuroinflammatory activity and regulating phagocytic function.